Genetic and Histological Alterations Reveal Key Role of Prostaglandin Synthase and Cyclooxygenase 1 and 2 in Traumatic Brain Injury–Induced Neuroinflammation in the Cerebral Cortex of Rats Exposed to Moderate Fluid Percussion Injury - Shojo, Hideki (Cell Transplant, 2017)
After the initial insult in traumatic brain injury (TBI), secondary neurodegeneration occurs that is intimately associated with neuroinflammation. Prostaglandin (PG) synthases and cyclooxygenase (COX) 1 and 2 may contribute to inflammation in the brain. Temporal and spatial expression features of PG and COX1 and 2 following trauma may guide the development of antineuroinflammation strategies. Here, we examined PG synthase signaling and COX1 and 2 gene expression levels and COX-1- and 2-positive cell types and their temporal localization in TBI-induced brain in an effort to reveal their participation in the disease’s evolving neuroinflammation. Using brain samples from the cerebral cortex of rats subjected to TBI model of lateral moderate fluid percussion injury (FPI), we sought to characterize the temporal (subacute TBI) and spatial (lateral cortical lesion) brain alterations accompanying the disease progression. Temporal gene expression changes of PG synthase signaling were compared between sham-operated and TBI-treated rats using microarray pathway analysis. Moreover, we examined COX1 and 2 expression patterns and their intracellular distribution in sham-operated and TBI-treated rats by immunohistochemistry. After FPI, COX1 and 2 gene expression levels, and PGE(2) synthase increased while PGD(2) synthase decreased, suggesting that PGE(2) and PGD(2) afforded contraindicative effects of inflammation and anti-inflammation, respectively. Immunohistochemical analyses showed that both COX1 and COX2 increased in a time-dependent manner in the brain, specifically in degenerating neurons of the cortex. Interestingly, the expression of COX cell type was cell-specific, in that COX1 was particularly increased in degenerating neurons while COX2 was expressed in macrophages. In view of the dynamic temporal and spatial expression of PG, COX1 and 2 gene expression and localization in the injured brain regulating PG synthase and COX1 and 2 activity will require a careful disease-specific tailoring of treatments to abrogate the neuroinflammation-plagued secondary cell death due to TBI.